Wage Policy According to the Labor Relations Law in Algeria - Ouarezki, Molod (Journal of Legal Studies and Researches, 2017)
Wages are of paramount importance, both at the organizational and individual levels. For organizations, they serve as a means to attract and retain qualified personnel, and more importantly, to increase productivity and ultimately achieve their goals. For individuals, wages represent a way to satisfy their various needs and foster a sense of appreciation from the organization. An individual's job satisfaction largely depends on the value of their monetary and in-kind compensation. Ensuring fair wages and implementing sound wage policies and benefits are crucial for the success of human resource management programs within an organization. This, in turn, fosters a positive relationship between employees and management. Indeed, many statistics indicate that most labor disputes with management stem from wage issues, given that wages significantly impact the economic and social standing of employees.